Comparative Government and Politics: An Introduction ed.6 - Rod Hague, Martin Harrop (Palgrave MacMilan, 2004)
Long established as the leading text in the field, the new sixth edition has been comprehensively updated, revised and rewritten throughout to take account of the impact and consequences of the events of September 11 2001 and other key developments of the early Twenty first century. Lively, accessible, student friendly and truly international in its coverage, the sixth edition includes the usual wide range of pedagogical features including full page country case studies, debate boxes and an increased number of charts, figures, tables and quotations throughout. The companion website for this new edition features an entirely new additional chapter (not included in the book) on political economy.